Design and fabrication of drain cover by casting process - Muhamad Amin, Ab Rasak (2012)
The study of sand casting is very important in order to carry out this project to ensure the student understand what to do. This project is about designing and fabricating the drain cover to expand the variety of design in market. This project is mainly about generating a new concept of drain covers for industrial purpose and long lasting. This project involves designing the drain cover by searching in the internet and on local hardware shop. With combination of idea from internet and refer to problem solving, this product design is a new idea. After completing design process, the real product is fabricated. After all process had been done, this drain cover may help user to understand the fabrication and designing process that involved in this project.